Bee products loaded polymeric films as a potential dressing material for skin treatments - Didem Demir; Oskay Kahraman; Semih Latif İpek; Seda Ceylan (Biofunctional Materials)
In this study, bee products such as honey, pollen, and propolis were directly incorporated into the polymer structure prepared based on chitosan and gelatin to obtain biofunctional thin films. Thin films were evaluated according to their potential as wound dressing material with different physicochemical analyses such as chemical structure, morphology, water retention capacity, wettability, degradability and water vapour permeability. The results obtained varied according to the type of bioactive substance. The contact angle and water vapour permeability properties of chitosan: gelatin films selected as control films were improved by adding bioactive substances. In addition, when evaluated in terms of biological properties, it was observed that the bee products loaded thin films exhibited high antioxidant and antibacterial activity. The preliminary optimization results obtained from this study may have the potential to be an initial idea for future studies to be carried out in the material-bee product composition, especially in material production processes.